Makna Religius Dalam Film Munafik 2 sebagai Media Pembelajaran Pendidikan Agama Islam: Analisis Semiotika Roland Barthes - Zainal Abidin, Sy. Moh. Ali; Sa'i, Mad (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze the construction of religious meaning in the film Munafik 2 using Roland Barthes’ semiotic approach at the levels of denotation, connotation, and myth. This research employs a qualitative approach with a library research design. Data were collected through documentation techniques, including repeated viewing, dialogue transcription, and identification of relevant scenes and symbols. Data analysis followed the Miles, Huberman, and Saldaña model, involving data reduction, data display, and conclusion drawing. The findings indicate that at the denotative level, the film explicitly represents Islamic teachings through characters’ dialogues and actions. At the connotative level, religious meanings evolve into representations of steadfast faith, eschatological hope, and critiques of deviant social practices. At the mythological level, the film constructs religious ideologies, including myths of faith resilience and eschatological narratives, while also deconstructing visual myths in society. The novelty of this study lies in the development of a religious semiotic perspective encompassing performative, transcendental, and reflective-critical dimensions in film analysis. These findings highlight that film functions not only as a representational medium but also as a producer of religious meanings and ideologies, with potential as a contextual learning medium in Islamic education.